Anesthesia outcomes in lysosomal disorders: CLN3 and GM1 gangliosidosis. Issue 3 (2nd December 2022) - Luckett, Amelia; Yousef, Muhammad; Tifft, Cynthia; Jenkins, Kisha; Smith, Andrew; Munoz, Andrea; Quimby, Rachel; Porter, Forbes D.; Dang Do, An Ngoc
Abstract: Natural history studies of pediatric rare neurometabolic diseases are important to understand disease pathophysiology and to inform clinical trial outcome measures. Some data collections require sedation given participants' age and neurocognitive impairment. To evaluate the safety of sedation for research procedures, we reviewed medical records between April 2017 and October 2019 from a natural history study for CLN3 (NCT03307304) and one for GM1 gangliosidosis (NCT00029965). Twenty‐two CLN3 individuals underwent 28 anesthetic events (age median 11.0, IQR 8.4–15.3 years). Fifteen GM1 individuals had 19 anesthetic events (9.8, 7.1–14.7). All participants had the American Society of Anesthesiology classification of II (8/47) or III (39/47). Mean sedation durations were 186 (SD = 54; CLN3) and 291 (SD = 33; GM1) min. Individuals with GM1 (6/19, 31%) were more frequently prospectively intubated for sedation (CLN3 3/28, 11%). Minor adverse events associated with sedation occurred in 8/28 (28%, CLN3) and 6/19 (32%, GM1) individuals, frequencies within previously reported ranges. No major adverse clinical outcomes occurred in 47 anesthetic events in pediatric participants with either CLN3 or GM1 gangliosidosis undergoing research procedures. Sedation of pediatric individuals with rare neurometabolic diseases for research procedures is safe and allows for the collection of data integral to furthering their understanding and treatment.